880 Rare Benign Chondromyxoid Fibroma of Rib, A Case Report; Is It Really Benign?. (12th October 2021) - Basak, B; Haragan, A; Shackcloth, M; Thekkudan, J
Abstract: Chondromyxoid Fibroma is a benign chondrogenic lesion accounting for less than one percent of the bone tumor; hence, likely to be misdiagnosed. Its presentation can vary from asymptomatic to pain, swelling, and movement restriction. The typical presentation includes a young male with a lesion commonly around the knee joint. However, we detail here an unusual presentation of this benign tumor in a 61-year male referred with chest pain and swelling. Histopathology can be very helpful in diagnosing this rare condition showing the characteristic patterns. Besides, as the tumor is locally aggressive, it can often be misinterpreted and treated as sarcoma. Moreover, it has a high recurrence rate. These characteristics make this rare tumor standout from the other benign tumors. Therefore, these cases need to be viewed thoroughly with a high index of suspicion pre-diagnosis and ensure adequate treatment and follow-up for successful management.